1986
DOI: 10.1093/jn/116.4.641
|View full text |Cite
|
Sign up to set email alerts
|

The Retardation of Aging in Mice by Dietary Restriction: Longevity, Cancer, Immunity and Lifetime Energy Intake

Abstract: We sought to clarify the impact of dietary restriction (undernutrition without malnutrition) on aging. Female mice from a long-lived strain were fed after weaning in one of six ways: group 1) a nonpurified diet ad libitum; 2) 85 kcal/wk of a purified diet (approximately 25% restriction); 3) 50 kcal/wk of a restricted purified diet enriched in protein, vitamin and mineral content to provide nearly equal intakes of these essentials as in group 2 (approximately 55% restriction); 4) as per group 3, but also restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
561
2
7

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 890 publications
(619 citation statements)
references
References 27 publications
27
561
2
7
Order By: Relevance
“…A recent study in mice has shown that changes in membrane composition are both proportional to the degree of CR and manifest within 1 month of onset of CR (Faulks et al 2006). Figure 4b illustrates the changes in PI of liver mitochondrial membranes of these mice relative to the changes in maximum longevity previously reported by others in a different mice strain but using the same CR regime (Weindruch et al 1986). …”
Section: Longevity Variation Within Speciesmentioning
confidence: 59%
See 2 more Smart Citations
“…A recent study in mice has shown that changes in membrane composition are both proportional to the degree of CR and manifest within 1 month of onset of CR (Faulks et al 2006). Figure 4b illustrates the changes in PI of liver mitochondrial membranes of these mice relative to the changes in maximum longevity previously reported by others in a different mice strain but using the same CR regime (Weindruch et al 1986). …”
Section: Longevity Variation Within Speciesmentioning
confidence: 59%
“…This treatment is the most common manipulation in the study of aging and was first described for rats in 1935 (McCay et al 1935). The degree of life span extension is linearly related to the amount of CR in both rats (Merry 2002) and mice (Weindruch et al 1986), but the precise mechanism by which CR extends longevity is not known (Masoro 2002). A common finding is that lipid peroxidation is reduced during CR (Habib et al 1990;Matsuo et al 1993).…”
Section: Longevity Variation Within Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calorie restricted rodents have a longer lifespan than their ad libitum fed counterparts (85). A recent human trial showed that caloric restriction resulted in the expected reduction in body weight and blood insulin (86).…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 99%
“…Despite many hypotheses, so far all have failed to explain the mechanism of action of different food restriction schedules, it remains well proven that the function organ systems are better and longer preserved in dietary restricted animals. Namely, the immunological response is markedly improved (4), renal and myocardial diseases (5) as well as the incidence of tumor mediated by free radicals (6,7) are reduced in food restricted animals.…”
Section: Introductionmentioning
confidence: 99%